2022
DOI: 10.3822/ijtmb.v15i2.705
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Effect of Reflexology and Swedish Massage on Restless Legs Syndrome and Sleep Quality in Patients Undergoing Hemodialysis: a Randomized Clinical Trial

Abstract: Background: Patients undergoing hemodialysis experience painful complications such as restless leg syndrome and poor sleep quality, which negatively affect their quality of life.Purpose: This study aimed to compare the effect of reflexology and Swedish massage on restless leg syndrome and sleep quality in patients undergoing hemodialysis. Method: This is a randomized clinical trial conducted on 90 patients undergo-ing hemodialysis. The two intervention groups received either foot reflexology (n = 30) or Swedis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 43 publications
(40 reference statements)
0
3
0
Order By: Relevance
“…This finding is consistent with the data in the present study. However, a study by Ghanbari et al on 90 hemodialysis patients showed that immediately after the intervention, restless leg syndrome and sleep quality in the foot reflexology group were significantly better than in the Swedish massage group (44). Contrary to the findings of the present study, Kawabata et al compared the effect of massage and aromatherapy on the quality of sleep in the palliative care ward and observed that massage and aromatherapy do not affect the quality of sleep and fatigue of patients in the palliative care ward (31).…”
Section: Discussionmentioning
confidence: 91%
“…This finding is consistent with the data in the present study. However, a study by Ghanbari et al on 90 hemodialysis patients showed that immediately after the intervention, restless leg syndrome and sleep quality in the foot reflexology group were significantly better than in the Swedish massage group (44). Contrary to the findings of the present study, Kawabata et al compared the effect of massage and aromatherapy on the quality of sleep in the palliative care ward and observed that massage and aromatherapy do not affect the quality of sleep and fatigue of patients in the palliative care ward (31).…”
Section: Discussionmentioning
confidence: 91%
“…Reflexology and Swedish massage, as complementary methods, can improve the restless leg syndrome and sleep quality of patients undergoing hemodialysis. However, foot reflexology massage had been more effective [29]. After a foot massage, 45% of them already have good sleep quality and 55% still have poor sleep quality.…”
Section: Discussionmentioning
confidence: 99%
“…Excess PTH secretion leads to bone resorption and weakening of the bones. Together, these abnormalities contribute to chronic kidney disease-mineral and bone disorder, a complex disorder that increases the risk of fractures, cardiovascular disease, and mortality in chronic kidney disease and ESRD patients (61,62).…”
Section: Chronic Kidney Disease-mineral and Bone Disordermentioning
confidence: 99%